2012
DOI: 10.3892/etm.2012.557
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between adipocytokines and cardiovascular risk factors in patients with type 2 diabetes mellitus

Abstract: Abstract. The aim of this study was to explore the relationship between serum profiles of adiponectin, leptin, resistin and visfatin and traditional and non-traditional cardiovascular risk factors in patients with type 2 diabetes mellitus (T2DM). A total of 85 patients with T2DM and 30 non-diabetic controls were enrolled in the study. Levels of adipocytokines (adiponectin, leptin, resistin and visfatin), lipids (total cholesterol, triglycerides), lipoproteins [HDL-cholesterol, LDL-cholesterol, lipoprotein (a)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 51 publications
6
55
0
1
Order By: Relevance
“…In turn, the resulting hyperinsulinemia may exacerbate obesity and further increase leptin levels, resulting in a diabetogenic positive feedback loop [36,37]. In support of this proposal, Uslu et al [35] found a close relationship between insulin and leptin levels in DM2 patients. Moreover, this group observed that leptin levels were positively correlated with TG, lipoprotein (a) [Lp (a)], Apo-A1, glucose, systolic blood pressure and diastolic blood pressure levels, and negatively with HDL-C levels in DM2 patients.…”
Section: The Role Of Leptin In Metabolic Syndrome and Diabetessupporting
confidence: 59%
See 1 more Smart Citation
“…In turn, the resulting hyperinsulinemia may exacerbate obesity and further increase leptin levels, resulting in a diabetogenic positive feedback loop [36,37]. In support of this proposal, Uslu et al [35] found a close relationship between insulin and leptin levels in DM2 patients. Moreover, this group observed that leptin levels were positively correlated with TG, lipoprotein (a) [Lp (a)], Apo-A1, glucose, systolic blood pressure and diastolic blood pressure levels, and negatively with HDL-C levels in DM2 patients.…”
Section: The Role Of Leptin In Metabolic Syndrome and Diabetessupporting
confidence: 59%
“…Paradoxically, markedly increased plasma leptin levels were found in obese individuals, suggesting a resistance to its effects on target organs when produced excessively [33]. Increased leptin levels were correlated both with BMI and IR in DM2 patients [34][35][36]. IR was found to indirectly contribute to hyperleptinemia [37], and it has been reported that the hyperinsulinemia that frequently accompanies obesity is likely to result in increased obesogenic gene expression and higher plasma leptin levels [31].…”
Section: The Role Of Leptin In Metabolic Syndrome and Diabetesmentioning
confidence: 89%
“…The subjects with hyper-duction, which is caused by impaired eNOS activity and expression, and increased production of superoxide anion and ADMA as well as vasoconstrictor factors, such as endothelin-1, and sympathetic nerve activation [33]. Uslu and colleagues reported that ADMA levels were correlated with hypoadiponectinemia and hyperleptinemia [34]. Adiponectin and leptin increases NO production in vascular endothelium and inhibits endothelial cell activation; both of these effects would be impaired by decreased adiponectin levels, leptin resistance and/or increased ADMA levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the validity of published data regarding its insulin-mimetic properties is under debate [9,10]. Despite this, it has been described that visfatin potentiated glucose-stimulated insulin secretion by pancreatic human islets [11] and elevated plasma levels of visfatin have been found in patients with type 2 [12,13] and type 1 diabetes mellitus [7].…”
Section: Introductionmentioning
confidence: 99%